2019
DOI: 10.1530/joe-18-0477
|View full text |Cite
|
Sign up to set email alerts
|

Influence of AT1 blockers on obesity and stress-induced eating of cafeteria diet

Abstract: Journal of Endocrinology240:1 65-79 V Gustaityte et al. ARB and stress eating of cafeteria diet AbstractBased on findings that treatment with AT 1 receptor blocker (ARB) prevents dietinduced obesity and that the activity of the hypothalamic-pituitary-adrenal (HPA) axis is stimulated by AngII and blocked by ARBs, we aimed to investigate whether ARB treatment can reduce stress-induced eating of cafeteria diet (CD), thus contributing to alterations in eating behavior. Sprague-Dawley rats were fed with chow or CD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
1
5
1
Order By: Relevance
“…Once a day, mice received TEL (8 mg/kg bw ) or vehicle by oral gavage in a volume of 5 µL/g body weight. TEL dosages were evaluated recently (Muller-Fielitz et al 2012) and have been confirmed in numerous studies both in rats (Miesel et al 2012, Muller-Fielitz et al 2014, Schuchard et al 2015, Winkler et al 2016, Gustaityte et al 2018 and in mice (Schuster et al 2018, Dapper et al 2019 to reveal antiobese effects. For administration, TEL was suspended in 10% gum arabic (Carl Roth GmbH, Karlsruhe, Germany), resulting in a suspension of 1.6 mg/mL TEL.…”
Section: Study Protocol (Part 1)mentioning
confidence: 96%
See 1 more Smart Citation
“…Once a day, mice received TEL (8 mg/kg bw ) or vehicle by oral gavage in a volume of 5 µL/g body weight. TEL dosages were evaluated recently (Muller-Fielitz et al 2012) and have been confirmed in numerous studies both in rats (Miesel et al 2012, Muller-Fielitz et al 2014, Schuchard et al 2015, Winkler et al 2016, Gustaityte et al 2018 and in mice (Schuster et al 2018, Dapper et al 2019 to reveal antiobese effects. For administration, TEL was suspended in 10% gum arabic (Carl Roth GmbH, Karlsruhe, Germany), resulting in a suspension of 1.6 mg/mL TEL.…”
Section: Study Protocol (Part 1)mentioning
confidence: 96%
“…We finally investigated whether the potency of ARBs to reduce the drive of the hypothalamic-pituitary-adrenal (HPA) axis contributes to a decrease in food intake. However, we recently demonstrated that stress-induced eating of high-calorie, good-tasting food only plays a minor role or none at all (Gustaityte et al 2018). As outlined in the introduction, the antiobese effect of ARBs is dependent on intact leptin signaling and leptin penetration across the BBB.…”
Section: Figurementioning
confidence: 99%
“…Once a day, mice received TEL (8 mg/kg bw ) or vehicle by oral gavage in a volume of 5 µL per gram body weight (bw) according to previous studies ( Schuster et al, 2018 ; Dapper et al, 2019 ; Rawish et al, 2020 ). TEL dosage was recently evaluated ( Muller-Fielitz et al, 2012 ) and has been confirmed in numerous studies both in rats ( Miesel et al, 2012 ; Muller-Fielitz et al, 2014 ; Muller-Fielitz et al, 2015 ; Schuchard et al, 2015 ; Winkler et al, 2016 ; Gustaityte et al, 2019 ) and in mice ( Schuster et al, 2018 ; Dapper et al, 2019 ; Rawish et al, 2020 ; Huber et al, 2021 ) to reveal anti-obese effects. For administration, TEL was suspended in 10% gum arabic (Carl Roth GmbH, Karlsruhe, Germany), resulting in a suspension of 1.6 mg/ml TEL.…”
Section: Methodsmentioning
confidence: 94%
“…Thus, AngII receptor (type 1) blockers (ARBs) such as telmisartan (TEL) and losartan (LOS) are well-established in the treatment of hypertension and heart failure, particularly with regard to their cardiometabolic benefits ( Michel et al, 2016 ). Beyond these beneficial actions, ARBs have been demonstrated to preventively and curatively lower obesity in rodents ( Muller-Fielitz et al, 2011 ; Miesel et al, 2012 ; Muller-Fielitz et al, 2012 ; Muller-Fielitz et al, 2014 ; Muller-Fielitz et al, 2015 ; Schuchard et al, 2015 ; Schuster et al, 2018 ; Winkler et al, 2018 ; Gustaityte et al, 2019 ; Rawish et al, 2020 ; Huber et al, 2021 ) and humans ( Kintscher et al, 2007 ). The anti-obese potency of ARBs occurs mainly after high dosages and is independent of their ability to reduce blood pressure ( Muller-Fielitz et al, 2011 ; Muller-Fielitz et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation